TH17 Cells in Autoimmunity and Immunodeficiency: Protective or Pathogenic? - Marwaha, Ashish; Leung, Nicole; McMurchy, Alicia N.; Levings, Megan (Frontiers in Immunology, 2012)
In 2005 a newly discovered T helper cell subset that secreted interleukin (IL)-17 became the center of attention in immunology. Initial studies painted Th17 cells as the culprit for destruction caused in many different autoimmune and auto-inflammatory diseases. Subsequently, the discovery of patients with primary immunodeficiencies in the IL-17 pathway taught us that Th17 cells have a critical role in defense against certain fungal and bacterial infections. Moreover, the paradoxical exacerbation of Crohn’s disease in the clinical trials of a Secukiumab (AIN457), a fully human neutralizing antibody to IL-17A, has cast into doubt a universal pro-inflammatory and harmful role for Th17 cells. Evidence now suggests that depending on the environment Th17 cell can alter their differentiation program, ultimately giving rise to either protective or pro-inflammatory cells. In this review will summarize the evidence from patients with immunodeficiencies, autoimmune, or auto-inflammatory disease that teaches us how the pro-inflammatory versus protective function of Th17 cells varies within the context of different human diseases.